DNA extraction and library preparation for NGS for diatoms - Vasquez Christodoulou, Marlen (My University, 2026)
▪ DNA extraction and quantification ▪ PCR and electrophoresis ▪ Library preparation ▪ Introduction to Mothur software Dr. Agnes Bouchez